Multiple neoplasia in a patient with Gitelman syndrome harboring germline monoallelic MUTYH mutation - Chan, Jason Yongsheng (2021)
Gitelman syndrome is a rare, recessively inherited disease characterized by chronic hypokalemia and hypomagnesemia as a result of defective electrolyte co-transport at the level of the distal convoluted tubule of the kidney. Here, we present the first report of a patient with Gitelman syndrome who developed multiple neoplasia including colorectal polyposis, synchronous colorectal cancers, recurrent breast fibroadenomata and a desmoid tumor. Whole-exome sequencing confirmed germline compound heterozygous mutations of c.179C > T and c.1326C > G in SLC12A3, and in addition, identified a monoallelic germline c.934-2A > G splice site mutation in MUTYH. In vitro, magnesium deficiency potentiated oxidative DNA damage in lymphoblastoid cell lines derived from the same patient. We postulate that monoallelic MUTYH mutations may manifest in the presence of cooperative non-genetic mechanisms, in this case possibly magnesium deficiency from Gitelman syndrome.